2021
DOI: 10.1136/neurintsurg-2021-017380
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular reperfusion of M2 occlusions in acute ischemic stroke reduced disability and mortality: ETIS Registry results

Abstract: BackgroundThe predictors of successful reperfusion and the effect of reperfusion after endovascular treatment (EVT) for M2 occlusions have not been well studied. We aimed to identify predictors of successful reperfusion and the effect of reperfusion on outcomes of EVT for M2 occlusions in current practice.MethodsPatients with acute ischemic stroke due to isolated M2 occlusions who were enrolled in the prospective multicenter Endovascular Treatment in Ischemic Stroke (ETIS) Registry in France between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Six two-armed studies compared the performance of SR and ASP techniques 16–21. Four three-armed studies compared the performance of SR+ASP to ASP and SR 22–25. Three two-armed studies compared the safety and efficacy of SR+ASP with SR or ASP alone 26–28…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six two-armed studies compared the performance of SR and ASP techniques 16–21. Four three-armed studies compared the performance of SR+ASP to ASP and SR 22–25. Three two-armed studies compared the safety and efficacy of SR+ASP with SR or ASP alone 26–28…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes results and characteristics of the studies included within the qualitative review. All the included studies, except Muszynski et al , provided raw data for successful recanalization 23 25. All studies provided data for thrombus location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are also in this range (83%), comparable to those of a recent meta-analysis (81%) [ 23 ], and higher than in the Hermes registry (71%) [ 6 ]. As far as the available literature shows, the chance for successful recanalization is equal or even higher for M2 than for M1 occlusions [ 9 , 14 , 24 , 25 ]. Compared to the STRATIS-Registry, the overall results for good clinical outcome and mortality within the GSR are less favorable, especially when considering M1 occlusions [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also obtained by IAT in a subgroup analysis of PROACT-II (Prolyse in Acute Cerebral Thromboembolism II) [ 4 ], with good clinical outcome achieved in only 28.6% of patients after best medical management, but in 48.6% of patients after MT. The impact of successful reperfusion has been shown in the ETIS Registry (excellent outcome (OR 2.3, 95% CI 0.98 to 5.36; p = 0.053), favorable outcome (OR 2.79, 95% CI 1.31 to 5.93; p = 0.007), and reduced 90-day mortality (OR 0.39, 95% CI 0.19 to 0.79; p < 0.01) [ 24 ], while Boyanpally et al found no additional benefit of MT compared to best medical management of M2 lesions [ 35 ].…”
Section: Discussionmentioning
confidence: 99%